THE CONCEPT OF IMAN AS A CLARITY FOR ASSESSMENT OF SHARIA FINANCE CRITERIA IN INDONESIA - Husaini, Hasan; Yusuf, Mahmud (Fakultas Agama Islam, Universitas Ibn Khaldun Bogor, 2023)
Clarity on sharia assessment criteria in Indonesia is important to build public confidence in the rapidly growing Islamic finance industry. While the challenge of the complexity of Islamic financial instruments exists, the development of shariah compliant criteria is necessary. This clarity is not only vital for financial institutions and industry players but also has a direct impact on investor and consumer confidence. This research uses the literature method with a normative approach. Data is obtained from primary and secondary sources, then processed and analyzed descriptively and qualitatively. The literature study method is used to study and review various documents and literature related to Islamic economics and sharia. The conclusion of this research highlights that the clarity of sharia criteria in the Islamic financial sector requires a holistic approach. In-depth consultations between Islamic jurists and the establishment of a specialized institution involving scholars, academics, and practitioners of Islamic economics are considered essential to ensuring that the assessment criteria reflect Islamic values. The IMAN concept, which encompasses Islamic values such as worship, muamalah, amanah, and ihsan, is considered to improve the performance assessment of Islamic banks by considering both financial and non-financial aspects. The focus on integrity, justice, and social responsibility in muamalah is expected to change the paradigm of Islamic bank performance assessment into a holistic evaluation that reflects Islamic values. The IMAN concept is not only aperformance assessment tool but also a clarification of sharia criteria in Islamic finance.